Fatty Acids Rich Extract From Clerodendrum volubile Suppresses Cell Migration; Abates Oxidative Stress; and Regulates Cell Cycle Progression in Glioblastoma Multiforme (U87 MG) Cells - Erukainure, Ochuko L.; Ashraf, Nadia; Naqvi, Asma S.; Zaruwa, Moses Z.; Muhammad, Aliyu; Odusote, Adenike D.; Elemo, Gloria N. (Frontiers in Pharmacology, 2018)
Glioblastoma multiforme (GBM) is a malignant primary type of brain cancer with high proliferation and metastasis rates due to involvement of the microglial cell. It is resistant against available chemotherapy. Many strategic protocols have been developed but prognosis and patient life has not improved substantially. In this study, the anti-metastatic and antioxidant effect of fatty acids from Clerodendrum volubile leaves were investigated in U87-MG (Human Glioblastoma Multiforme) cell lines. The extracted fatty acids were incubated with U87-MG cells for 48 h. The anti-proliferative effect was determined by MTT assay, while apoptosis and cell cycle were analyzed with BD FACSCalibur. The transwell assay protocol was utilized in the analysis of cell migration and invasion. The treated cell lines were also assessed for reduced glutathione (GSH) level, catalase, superoxide dismutase (SOD) and lipid peroxidation. The fatty acid extract showed significant inhibitory activity on cell proliferation and cell cycle progression, mitigated oxidative stress, and suppressed migration and invasion in U-87 MG cell lines. These results give credence to the therapeutic potential of this plant against cancer, especially GBM.